Studies towards the synthesis of complex amino acids derived from microsclerodermins - Rathi, AH (2012)
This thesis describes the studies towards the synthesis of β-amino acids found in the microsclerodermins, a family of complex macrocyclic hexapeptides. These β-amino acids have four or five contiguous stereocentres and an aliphatic side-chain. The synthetic route utilised an aminohydroxylation reaction to install the most challenging moiety in the structure - the 1,2- amino alcohol. The work aimed to construct the core structure (five contiguous stereocentres) of the β-amino acids and install the side-chain later to enable the synthesis of multiple members (A, B, F, G, H and I) of the microsclerodermin family. The synthesis started with Roche ester, which contained the first methyl stereocentre. It was converted to the diene precursor in four high yielding steps. The next two stereocentres were installed via a Sharpless asymmetric dihydroxylation. With the appropriate protecting groups in place, the remaining two stereocentres were to be installed via a Sharpless asymmetric aminohydroxylation. Various reported reagents and conditions were used to effect the transformation, but the attempts were unsuccessful. This forced us to alter our synthetic plans, and the revised synthetic route involved the use of the tethered aminohydroxylation (TA) reaction developed by the Donohoe group. After the development of an efficient protocol to prepare the TA-precursor, the alkene, with three stereocentres already in place, was successfully converted to the desired stereopentad via the TA-reaction (10 steps, 11% overall yield). With the stereopentad in hand, installation of the side-chain of the β-amino acids through an alkenyl or alkyl linkage was investigated. For alkenyl-linked side-chains, the appropriate aldehyde was synthesised, but attempts to effect the transformation via a Horner-Wadsworth- Emmons reaction or a Witting reaction failed. With lessons learnt from those, we then focused our efforts on installing an alkyl-linked side-chain. In this case, we were able to install a side- chain via a copper-mediated displacement reaction, which gave us a protected form of the precursor of the β-amino acid of microsclerodermin B. Finally, various efforts to study the reactivity of the stereopentad and the investigations into finding the most effective set of protecting groups have been used to propose a synthetic route for the incorporation of the β- amino acid into the macrocycle.